PengaruhTata kelola perusahaan, Profitabilitas, Kebijakan Dividen, Intensitas penelitian dan Pengembangan terhadap Nilai Perusahaan Pada Perusahaan Manufaktur yang Tercatat di Bursa Efek Indonesia Periode Tahun 2009 – 2011 - Panca Wahyuningsih; Agus Budi Purwanto (STIE Pelita Nusantara Semarang, 2013)
The purpose of most major companies according to the theory of the firm is to maximize the value of company.Company can increase the prosperity of the owner or the shareholders by increasing the value of the company, both internally and externally. This study aims to determine the effect of corporate governance, profitability, dividend policy, and research and development intensity on firm value.The sample of this study is manufacturing companies listed in Indonesia Stock Exchange during the period 2009-2011. With purposive sampling method to obtain 10 companies that meet the criteria, resulting in 30 observations. Data were analyzed using analysis Ordinary least Square.The results of the study draws conclusions that simultaneous (Test - F) All independent variables (corporate governance, profitability, dividend policy, and R & D intensity affects the dependent variable (firm value) . Partial (t-test) there are four variables that affect the value of company board size is variable (sig 0.000) , Independent board (sig 0.039) , Profitability (sig 0.048) , dividend policy (sig 0.020). Two other variables that do not affect the value of the company is Board intensity (sig 0.022) and R & D intensity (sig 0.077).